Analysis of Maritime Single Window System Implementation on Single Submission (SSM) Carriers in Indonesia - Tiur Margaretha Malau; Alia Nabilah Putri; Dhiya Ratna Sari Khaerunnisa; Ivan Darmawan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The development of information technology has led to the rapid growth of the internet as it provides a fast communication medium for various types of information. Recently, the internet has brought about changes, including the emergence of the latest technology in public services that the government uses as a new technology-based approach, known as e-government. The implementation of e-government itself has been carried out in many forms, including what we will discuss, namely the Maritime Single Window system. The Maritime Single Window (MSW) system, also known as the Maritime Single Window System, is an integrated system that enables the exchange of data or information between parties involved in port or maritime activities. The research concludes that the impact of MSW is a driving factor for the advancement of Indonesia's maritime sector. Although challenges still exist, positive achievements indicate the significant potential of this system to accelerate economic growth, improve operational efficiency, and make Indonesia's maritime sector more competitive globally. This research was conducted using a qualitative descriptive method, with secondary data sources obtained from various sources such as books, journals, documents, and other related media.